Mapping out model bisnis sharing economy pada unicorn asal Indonesia - Hanifah, Hanifah; Hayati, Cucu; Sadiqin, Amin (Nur Science Institute, 2024)
This research dissects the business models built by 3 (three) companies ranked in the TOP 20 unicorns from Indonesia based on research conducted by CB Insight, namely Gojek, Tokopedia, and Traveloka. Researchers employed exploratory methods, comparative analysis techniques and utilized the Business Model Canvas and Stakeholder Relationship Model as instruments in data collection. Data were obtained from secondary sources, including online interviews and literature reviews. This research reveals that companies offering digital goods and services implement the concept of sharing assets to achieve zero marginal cost. The research findings also uncover that an increasing number of Gojek passengers, Traveloka guests, and Tokopedia customers lead to an increase in the number of business groups (positive network effect). Moreover, an increase in Gojek drivers, Traveloka hosts, and Tokopedia sellers results in higher competition within those groups (negative network effect).